The Effect of Health Educational Session on Raising Pregnant Woman’s Awareness and Improving their Attitude Toward Gestational Diabetes - Hind Al Ghadeer; Hind Mohmmad Kanoori; Farida Habib; Nagwa Afefy (GLOBAL HEALTH SCIENCE GROUP, 2022)
Gestational diabetes mellitus (GDM) is the most common complication during pregnancy. It is characterized by elevated blood sugar level with previous normative blood sugar level. It appears between 24 to 28 weeks of gestation, which is detected as a part of antenatal visits. The aim of this study is to assess the effectiveness of a health educational session on raising pregnant woman’s health awareness and their attitude toward Gestational Diabetes. A quasi experimental design was used to conduct the study. A convenient sample of 90 Saudi women who attended Obstetrics & Gynecology outpatient clinic at (KAMC-MNGHA-Riyadh) were included. Data was collected by using self-administered close ended questionnaire which consisted of four parts: Socio-demographic characteristics, obstetrical history, knowledge assessment, and attitude assessment (Pre-Post assessment).The educational session lasted for 20 – 25 minutes. There was a significant improvement in the total knowledge score before and after educational session about gestational diabetes (total knowledge score (P = 0.000). Out of the total sample (20 %) of the subjects had poor knowledge in the pre-test compared to (100%) in the post test. Also, there was significant differences in total attitude score before and after the session (p=0.013). Out of the total sample (24.4 %) of the subjects had negative attitude in the pretest compared to 8.9%in the post test. However, there were no significant differences in the knowledge mean score of the women across their Socio-demographic or obstetrical history. The study presented substantial findings that educational session significantly increased the level of knowledge and improve the attitude of women towards gestational diabetes.